A marxist reading on the disintegration of American families in Sam Sherpard's true west and curse of the starving class - Majeed, Abdulhameed A. (2015)
American society began to experience the effects of capitalism in the twentieth century. The whole system of social values was modified by capitalist influence which pervaded the American society. People started to be valued in terms of commodity, and the struggle between the capitalist class and the working one is intensified. The materialistic struggle invaded the family household, and modern American drama depicted the effects of the capitalist culture of consumption on family relationships. Family members perceived that they were ‘things’ and ‘commodities’ in Twentieth- century America. Thus, this research tries to achieve three objectives. The first objective is to analyse class conflict in the selected plays as a materialistic struggle between capitalists and the proletariat in the face of the American Dream. The second objective is to examine the characters’ capitalist ideology. Capitalist ideology wants the public to believe that the American Dream is still alive and attainable. Objective three is to explore the capitalist ideology which is inherent in the characters’ behaviours to argue for a distorted American Dream. Accordingly, the study approaches the title in a Marxist approach, showing the superficialities and discrepancies of the capitalist system. It focuses on the dysfunctions of the family due to the materialistic conceptions of its members. Sam Shepard depicted the family deterioration and cut of communication in his plays in accordance to the capitalist conception of family members life. The Marxist reading of the plays selected shows the vulgarity and futility of the capitalist values of the Americans in their endeavors to cope with the materialistic standards of success of the American Dream.